The last good man : a novel - Kazinski, A. J. (Scribner, 2012)
A story based on the Jewish legend about how the world is always protected by 36 people follows the sudden deaths of dozens of humanitarians who each bear a bizarre tattoo and whose untimely ends are investigated by Copenhagen detective Niels Benzon, who would save the remaining protectors.